PEMANFAATAN INTERNET UNTUK PENGHIDUPAN DI KALANGAN PEMUDA PEDESAAN - Yusup, Pawit; Komariah, Neneng; Prahatmaja, Nurmaya; CMS, Samson (BACA: Jurnal Dokumentasi dan Informasi, 2019)
This study aims to examine more deeply about the use of the internet for entrepreneurial purposes or livelihoods among rural youth. The method used is observation and in-depth interviews with 20 business informants in this internet sector. The results of the study illustrate that: (a) viewed from the aspect of knowledge, business people understand correctly that the internet is the main media used to find information and sources of livelihood information; (b) viewed from the aspect of motivation, they are encouraged to use the internet for entrepreneurship because it is very easy to learn; (c) judging from the aspects of behavior and experience, business people in this sector feel very disturbed when there are a network disorder.